Integrated Analysis of Metabolome and Transcriptome Data for Uncovering Flavonoid Components of Zanthoxylum bungeanum Maxim. Leaves Under Drought Stress - Hu, Haichao; Fei, Xitong; He, Beibei; Luo, Yingli; Qi, Yichen; Wei, Anzhi (Frontiers in Nutrition, 2022)
Zanthoxylum bungeanum Maxim. leaves (ZBLs) are rich in flavonoids and have become popular in nutrition, foods and medicine. However, the flavonoid components in ZBLs and the mechanism of flavonoid biosynthesis under drought stress have received little attention. Here, we performed an integrative analysis of the metabolome and transcriptome of ZBLs from HJ (Z. bungeanum cv. “Hanjiao”) and FJ (Z. bungeanum cv. “Fengjiao”) at four drought stages. A total of 231 individual flavonoids divided into nine classes were identified and flavones and flavonols were considered the most abundant flavonoid components in ZBLs. The total flavonoid content of ZBLs was higher in FJ; it increased in FJ under drought stress but decreased in HJ. Nine-quadrant analysis identified five and eight differentially abundant flavonoids in FJ and HJ leaves, respectively, under drought stress. Weighted gene correlation network analysis (WGCNA) identified nine structural genes and eight transcription factor genes involved in the regulation of flavonoid biosynthesis. Moreover, qRT-PCR results verified the accuracy of the transcriptome data and the reliability of the candidate genes. Taken together, our results reveal the flavonoid components of ZBLs and document changes in flavonoid metabolism under drought stress, providing valuable information for nutrition value and food utilization of ZBLs.